2018
DOI: 10.3892/etm.2018.6683
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dexpanthenol against cisplatin‑induced hepatotoxicity

Abstract: The aim of the present study was to investigate the protective effect of dexpanthenol (Dexp) against cisplatin (Cis)-induced hepatotoxicity. Thirty-two Sprague Dawley rats were divided into four groups: Control group (n=8), Dexp group (n=8, 500 mg/kg/ip/daily single dose/3 days Dexp), Cis group (n=8, 7 mg/kg/ip/single dose Cis) and Cis+Dexp group (n=8, 500 mg/kg/ip/daily single dose/3 days Dexp +7 mg/kg/ip/single dose Cis). MDA, CAT, GSH, GSH-Px, TOS, TAS, OSI, Total Nitrit, IL-1β, IL-6 and TNF-α levels were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Some samples showed peri-ductal inflammatory cell infiltrate. There finding was in full agreement with those previously reported by Bilgic et al [39]. They found that the most prominent alteration in the liver of CDDP-treated animals' group was sinusoidal congestion.…”
Section: Photomicrographs Of Immunohistochemical Staining Ofsupporting
confidence: 93%
See 2 more Smart Citations
“…Some samples showed peri-ductal inflammatory cell infiltrate. There finding was in full agreement with those previously reported by Bilgic et al [39]. They found that the most prominent alteration in the liver of CDDP-treated animals' group was sinusoidal congestion.…”
Section: Photomicrographs Of Immunohistochemical Staining Ofsupporting
confidence: 93%
“…The quantitative assessment of the Caspase-3 immunoexpression in the liver revealed that it was significantly increased in this group compared to the control one. This finding was supported by this of Bilgic et al [39] who reported that CDDP group showed a significant increase in the caspase-3 expression in the liver [39].…”
Section: Photomicrographs Of Immunohistochemical Staining Ofsupporting
confidence: 67%
See 1 more Smart Citation
“…It unleashes its anticancer action through formation of cisplatin‐DNA adduct by intrastrand cross‐links due to interaction with cancer cell DNA purine bases eventually leading to p53 activation, cell cycle arrest and induction of apoptosis (Calcabrini, Maffei, Turrini, & Fimognari, 2020; Dasari & Bernard Tchounwou, 2014). Despite its potent antineoplastic efficacy, the constraint to its clinical utility is the development of organ toxicity, including nephrotoxicity, neurotoxicity, hepatotoxicity, myelosuppression, cardiotoxicity, pancreatic and testicular damage (Bami et al., 2017; Bilgic et al., 2018; El‐Hawwary & Omar, 2019; Stošić et al., 2020). In the emerging papers, CIS‐induced damage to testes and hormonal imbalance has been suggested a chief side effect because it has been clinically associated with infertility (Altuner, Gulaboglu, Yapca, & Cetin, 2013; Mercantepe, Unal, Tümkaya, & Yazici, 2018; Sabanegh & Ragheb, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DXP has an “antioxidative,” “anti‐inflammatory” effect and a cellular repair capability 2,4 . To date, DXP has been used in numerous diseases including hepatotoxicity, wound healing, nephropathy without serious side effects 5‐7 …”
mentioning
confidence: 99%